Interdisciplinary utilization of IT - Neradová, Soňa; Zitta, Stanislav (IEEE (Institute of Electrical and Electronics Engineers), 2017)
This article describes a project realized in laboratory seminars. The aim was to practically show students utilization of information technologies in a non-technical discipline. The project involved observing and monitoring breathing of chosen plants. Recorded data were subsequently analysed into several conclusions. The goal was to design and practically build a solution which would enable to record the collected data from the sensors. The designed system contained wireless module and sensors for measuring temperature, humidity and CO2 concentration. The collected data were transferred to the web server ThingSpeak. Data values could be studied through an internet browser and also downloaded for further analysis. The major founding is that interdisciplinary skills led to successful creation of financially undemanding functional unit, which enabled automation of the data collection. The students were given the opportunity to design an IT platform, to implement and to analyse collected data. Individual components of the project required combination of the skills from informatics, physics, biology and mathematics.
Interdisciplinarní použití IT
Keywords: Data collection; Interdisciplinary skills; ThingSpeak; Sběr dat, Interdisciplinární dovednosti, ThingSpeak